Study of the Photostability of Sodium Montelukast Under Controlled Stress Conditions - Sousa, Kamila Viana; Dias, Lucas Danilo (CIPEEX, 2025)
Montelukast Sodium is a drug widely used in the treatment of respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD). Although its therapeutic efficacy is well established, the stability of the drug under different environmental conditions, especially exposure to light, has raised increasing concerns. This study evaluated the photostability of montelukast sodium under different wavelengths and light doses. Drug degradation was monitored using UV-Vis spectrophotometry and high-performance liquid chromatography (HPLC). The results provide essential information for optimizing the storage and handling conditions of montelukast sodium, ensuring its efficacy and safety. This study is essential for the development of guidelines to ensure the drug’s stability throughout clinical use.